Commoning care: Feminist degrowth visions for a socio-ecological transformation - Dengler, Corinna; Lang, Miriam (Feminist Economics, 2022)
This paper addresses the question of how to organize care in degrowth societies that call for social and ecological sustainability, as well as gender and environmental justice, without prioritizing one over the other. By building on degrowth scholarship, feminist economics, the commons, and decolonial feminisms, we rebut the strategy of shifting yet more unpaid care work to the monetized economy, thereby reinforcing the separation structure in economics. A feminist degrowth imaginary implies destabilizing prevalent dichotomies and overcoming the (inherent hierarchization in the) boundary between the monetized economy and the invisibilized economy of socio-ecological provisioning. The paper proposes an incremental, emancipatory decommodification and a commonization of care in a sphere beyond the public/private divide, namely the sphere of communitarian and transformative caring commons, as they persist at the margins of capitalism and are (re-)created by social movements around the world.HIGHLIGHTS Degrowth aims at creating human flourishing within planetary boundaries.As feminist degrowth scholarship, this study discusses degrowth visions for care work.It problematizes the shifting of yet more unpaid care work to the monetized economy.Instead, it proposes collective (re)organization in the sphere of the commons.Caring commons are no automatism for a gender-just redistribution of care work.
Keywords: approches et analyses; care; discipline; décroissance; environnement; féminisme décolonial; projet charge mentale; sciences de la gestion; thématiques; travail; travail du care; économie

Une écologie décoloniale - Ferdinand, Malcom (Éditions du Seuil, 2019)
Une colère rouge recouvre le ciel. Les vagues s’agitent, l’eau monte, les forêts tombent et les corps s’enfoncent dans ce sanguinaire gouffre marin. Les cieux tonnent encore devant ce spectacle : le monde est en pleine tempête. Derrière sa prétention d’universalité, la pensée environnementale s’est construite sur l’occultation des fondations coloniales, patriarcales et esclavagistes de la modernité. Face à la tempête, l’environnementalisme propose une arche de Noé qui cache dans son antre les inégalités sociales, les discriminations de genre, les racismes et les situations (post)coloniales, et abandonne à quai les demandes de justice. Penser l’écologie depuis le monde caribéen confronte cette absence à partir d’une région où impérialismes, esclavagismes et destructions de paysages nouèrent violemment les destins des Européens, Amérindiens et Africains. Le navire négrier rappelle que certains sont enchaînés à la cale et parfois jetés par-dessus bord à la seule idée de la tempête. Tel est l’impensé de la double fracture moderne qui sépare les questions coloniales des destructions environnementales. Or, panser cette fracture demeure la clé d’un « habiter ensemble » qui préserve les écosystèmes tout autant que les dignités. Telle est l’ambition d’une « écologie décoloniale » qui relie les enjeux écologiques à la quête d’un monde au sortir de l’esclavage et de la colonisation. Face à la tempête, ce livre est une invitation à construire un navire-monde où les rencontres des autres humains et non-humains sur le pont de la justice dessinent l’horizon d’un monde commun.
Keywords: amériques; approches et analyses; caraïbes; com5170; cours; environnement; fem3600; féminisme décolonial; histoire et politique; premier cycle; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Sous le développement, le genre - Verschuur, Christine; Guérin, Isabelle; Guetat-Bernard, Hélène (IRD Éditions, Institut de Recherche pour le Développement, 2015)
Du site de l'éd. : Ignorée, invisible, la question du genre reste cachée sous le développement. Et pourtant, comprendre le développement n'est pas possible sans une perspective de genre. Cet ouvrage, didactique, montre en quoi et comment le concept de genre permet de revisiter les études de développement. Le genre permet de comprendre la construction historique, sociale et culturelle des diffé- rences et des inégalités. Il offre des outils pour une analyse critique du système capitaliste globalisé. Le genre, inscrit dans le féminisme, permet aux catégories dominées et marginalisées, en particulier les femmes mais pas seulement, de faire entendre leurs voix. Dans le contexte actuel de crise globale et d'accroissement des inégalités, il propose des pistes pour renouveler la pensée sur le développement, mais aussi pour agir autrement. Combinant diverses disciplines et thématiques, cet ouvrage montre que la portée heuristique du genre ne se limite pas aux domaines habituellement considérés comme féminins (l'éducation, la famille, le social, la santé de la reproduction, etc.) mais s'étend à tous les domaines (le politique, le droit, la sécurité, la diplomatie, l'économie, etc.).Ce livre met aussi en évidence la diversité et l'enrichissement mutuel des diverses traditions de recherche entre le monde francophone, anglophone et hispano- phone. Il s'adresse particulièrement aux personnes étudiantes, chercheures et enseignantes, militantes, chargées de programme dans des organisations de coopération et représentantes des pouvoirs publics au Nord et au Sud.
Le chapitre “Une histoire du développement au prisme du genre. Perspectives féministes et décoloniales” de Verschuur, Christine, et al. 2015, pp. 43-71. a été donné en lecture dans le cours POL4022
Keywords: agriculture; anthropologie; approches et analyses; corps; cours; discipline; droit; environnement; féminisme décolonial; féminisme matérialiste; justice sociale; migration; pol4022; premier cycle; rapports sociaux de sexe; relations internationales; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sciences humaines; sociologie; thématiques; travail; économie

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (UBC Press, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry – Indigenous feminism – is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays – What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? – cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."–Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."– Résumé de l'éditeur.
Le texte de Tsosie, Rebecca (2011). Native Women and Leadership: An Ethics of Culture and Relationship a été donné en lecture au cours POL4105.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires

Genre, mouvements populaires urbains et environnement - Verschuur, Christine (Graduate Institute Publications, 2007)
Le désordre urbain et les défis environnementaux que nous connaissons ne sont pas perçus ni vécus pareillement aux Suds et aux Nords, par les femmes et les hommes, par les puissants et les exclus. Les mouvements populaires urbains et de lutte pour l'environnement participent de la réflexion sur les changements de paradigme de développement qui sont urgents et nécessaires. La perspective de genre donne des clés de lecture pour comprendre comment les asymétries féminin-masculin structurent la perception et l’organisation concrète de la vie sociale. La forte présence des femmes dans les organisations urbaines et de lutte pour l’environnement est généralement peu ou pas reconnue. Ce livre explore certains mouvements populaires urbains, qui participent au travail de prise de conscience et de revendications de droits et qui permettent ainsi d'envisager des alternatives sur des territoires de vie, sans plus attendre.
Keywords: 2000 à aujourd'hui; approches et analyses; changements climatiques; environnement; féminisme décolonial; histoire et politique; intersectionnalité; justice climatique; justice sociale; outils; ouvrages de références; projet charge mentale; périodes historiques; thématiques; écoféminisme

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme